Cytomegalovirus infection after acute rejection therapy in seropositive kidney transplant recipients. Issue 3 (9th May 2014) - Lee, Y.‐M.; Kim, Y.H.; Han, D.J.; Park, S.‐K.; Park, J.S.; Sung, H.; Hong, H.‐L.; Kim, T.; Kim, S.‐H.; Choi, S.‐H.; Kim, Y.S.; Woo, J.H.; et al.
Abstract Background Acute rejection (AR) after solid organ transplantation has been known to be a risk factor for cytomegalovirus (CMV) infection. However, data regarding the risk for CMV infection during and after anti‐rejection therapy are limited. This study investigated whether the risk of CMV infection and disease within 6 months of kidney transplantation (KT) increases in CMV‐seropositive KT recipients who develop AR. Methods A total of 992 seropositive KT recipients, including 75 patients (8%) who developed AR within 6 months after KT and 917 patients (92%) who did not, were recruited between May 2007 and April 2012. Results No significant difference was found in the incidence of CMV infection between the groups (AR group, 13% [10/75] vs. non‐AR group, 10% [92/917], P = 0.37). The number of KT recipients in each group receiving preemptive therapy for CMV was similar (5% [4/75] vs. 6% [53/917], P > 0.99). While the incidence of CMV syndrome was comparable (0% [0/75] vs. 1% [12/917], P > 0.99), the incidence of tissue‐invasive CMV disease (8% [6/75] vs. 3% [27/917], P = 0.04), particularly gastrointestinal CMV disease, was significantly greater in patients who experienced AR. No CMV‐related mortality occurred in either group. AR (odds ratio, 2.81; 95% confidence interval, 1.08–7.29; P = 0.03) was an independent risk factor for tissue‐invasive CMV disease within 6 months of KT. Conclusions A high index of suspicion and active evaluation for tissue‐invasive CMV disease in KT recipients suffering AR may be necessary to ensure appropriate treatment.